R. S. Ball's Mechanics: bringing Newton to the masses? - Hollings, C (Cambridge University Press, 2017)
In 1879, the Irish astronomer Robert Stawell Ball published a slim book entitled simply Mechanics [1]. This book appeared as part of the series of ‘London Science Class-Books’, published by Longmans, Green & Co. These books were intended as elementary science texts for use in schools, and, as a consequence, their mathematical content was quite basic — even for those books on supposedly mathematical topics. In this article, I will look at Ball’s handling of his subject, and compare his book to its distant ancestor: Newton’s Principia.